Countercyclical Liquidity Policy and Credit Cycles: Evidence from Macroprudential and Monetary Policy in Brazil - Joao Blanco Barroso; Rodrigo Barbone Gonzalez; José-Luis Peydró; Bernardus Nazar van Doornik (Universitat Pompeu Fabra (upf), Department of Economics and Business, 2019)
We show that countercyclical liquidity policy smooths credit supply cycles, with stronger crisis effects. For identification, we exploit the Brazilian supervisory credit register and liquidity policy changes on reserve requirements, that affected banks differentially and have a monetary and prudential purpose. Liquidity policy strongly attenuates both the credit crunch in bad times and high credit supply in booms. Strong economic effects are twice as large during the crisis easing than during the boom tightening. Finally, in crises, liquidity easing: increase less credit supply by more financially constrained banks; and collateral requirements increase substantially, especially by banks providing higher credit supply.
Keywords: E51; E52; E58; G01; G21; G28; 330; liquidity; reserve requirements; credit cycles; macroprudential and monetary policy